Factors determining the myopia control effect of an orthokeratology lens: A two‐year multi‐level model. (2nd May 2022) - Chen, Xiaohang; Xiong, Yan; Liu, Fengyang; Wang, Jianglan; Yang, Bi; Liu, Longqian
Abstract: Purpose: A multi‐level model was used to analyse factors, including environmental factors, affecting the controlling effect of orthokeratology on myopia progression. Methods: A 2‐year prospective study was conducted in the West China Hospital, Sichuan University. Age, sex, height, baseline spherical equivalent refraction, choroidal thickness, axial length and other biometric ocular parameters were collected. Additionally, data on the following environmental factors were obtained: near‐work distance and time, sleep time and time spent outdoors. After the baseline measurements, participants were followed up every 3 months for 2 years of lens wear. The primary outcome measure was axial length elongation over 2 years of orthokeratology. All variables were included in a univariate, three‐level analysis model with inclusion in the final multivariate multi‐level model if statistically significant. Results: Thirty‐three participants (average age 9.73 ± 1.55 years) were included in this study. During the 2‐year period of lens wearing, binocular changes in axial length increased significantly from the ninth month and continued until the end of the follow‐up. Changes in axial length after 2 years of lens wearing were 0.44 ± 0.30 mm and 0.37 ± 0.26 mm in the right and left eyes, respectively (both p < 0.001). Based on the 2‐year multi‐level model, age, sex, baseline spherical equivalent refraction, flatter keratometry meridian and near‐work time influence the effect of orthokeratology. Conclusions: This is the first study to use a multi‐level model to analyse factors, including environmental factors, that affect myopia control using orthokeratology. These results showed that younger age, being female, having lower myopia at baseline, a steeper flattest keratometry meridian and no more than 5 h of near work per day were associated with better myopia control effect using orthokeratology over a 2‐year treatment period.